The Efforts to Prevent Radicalism Based on The Madura Locality in Islamic Religious Education Courses in State Universities - AM, Mukhlishah; Sholihah, Ni'matus (Pascasarjana Universitas KH. Abdul Chalim, 2025)
This research is an effort to find out the radicalism movement in state universities and prevention efforts through the process of Islamic religious education at Trunojoyo University, Madura. The research approach method is phenomenology-ethnographic. On the scientific field, this research includes education and socio-religious research, namely academic studies of education, social religion and religion. Data are collected by observation, interviews, and a series of identification processes. The results showed first, the learning process of Islamic Religious Education at Trunojoyo University, Madura, was carried out as the coordinator of the General Course, at the Islamic Faculty. The learning process is conducted by face-to-face meetings in the classroom. Besides, there is an obligation for students to take part in mentoring activities outside the classroom as the reinforcement of religious character education for students. Second, the characteristics of the radicalism movement have generally started to grow and have a strong basis among students, and some lecturers. For further prevention, in the learning process of Islamic Religious Education, approaching and internalizing are aimed to counter radicalization movement. As in the matter of how to embody Islam in Indonesia, students are required to analyze how Islamic teachings in the context of modernity and Indonesian-ness by presenting the results of work projects on how to implement Islamic teachings. The effort process of deradicalization is built among them, both lecturers and mentees by spreading the moderation aspects adopted, as well as through psychological approaches, both arising from students and from lecturers.